Transverse-momentum resummation for top-quark pair production at the LHC - Stefano Catani; Massimiliano Grazzini; Hayk Sargsyan (Journal of High Energy Physics, 2018)
Abstract We consider transverse-momentum resummation for top-quark pair production in hadron collisions. At small transverse momenta of the top-quark pair, the logarithmically-enhanced QCD contributions are resummed to all orders up to next-to-leading logarithmic accuracy. At intermediate and large values of transverse momenta, the resummation is consistently combined with the complete result at fixed perturbative order. We present numerical results for the transverse-momentum distribution of top-quark pairs at LHC energies. We perform a detailed study of the scale dependence of the results to estimate their perturbative uncertainty. We comment on the comparison with ATLAS and CMS data.